1999
DOI: 10.1076/mcmd.5.4.351.3678
|View full text |Cite
|
Sign up to set email alerts
|

Model Based Design of a Novel Process for Nitrogen Removal from Concentrated Flows

Abstract: A new process for biological nitrification was developed that is operated in a single aerated reactor at relatively high temperature and pH. This process, termed SHARON, was designed to achieve substantial ammonia conversion at high reaction rates for relatively concentrated flows, rather than to meet strict effluent standards. First large scale applications that are under construction now, aim at treating reject water from a sludge digestion unit. The SHARON process operates without sludge retention, and ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
154
2
14

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(178 citation statements)
references
References 6 publications
8
154
2
14
Order By: Relevance
“…As expected (Hellinga et al 1999), the oxidation rates of AOB were higher than those of NOB (i.e. 3.3 mgNH 4 -N/gVSS.h and 2.9 mg NO 2 -N/gVSS.h at 35 o C for AOB and NOB, respectively).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…As expected (Hellinga et al 1999), the oxidation rates of AOB were higher than those of NOB (i.e. 3.3 mgNH 4 -N/gVSS.h and 2.9 mg NO 2 -N/gVSS.h at 35 o C for AOB and NOB, respectively).…”
supporting
confidence: 83%
“…The AMS3 model (Henze et al, 2000), the structure of the nitrification and denitrification model developed by Hellinga et al (1999), and the modified ASM3 model developed by Iacopozzi et al (2007) were adapted to describe the two step nitrification-denitrification processes. However, unlike in ASM3, no storage processes were considered in the anoxic growth kinetics since it has been shown that methanol is not taken up and stored as intracellular polymers but directly consumed instead (Purtschert and Gujer, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…is the predominant (70%) species in seawater. Furthermore, the amount of nitrate in the outlet of the biofilter is greater than in the inlet due to the biological oxidation of NH 4 + and NO 2 -by the nitrification reactions (Hellinga et al, 1999). Therefore, autotrophic nitrifying bacteria are also present in the filter.…”
Section: Nitrogenmentioning
confidence: 99%
“…Technologies such as SHARON process (Single reactor High activity Ammonia Removal over Nitrite) (Hellinga et al, 1999) and SHARON-ANAMMOX process (combination of partial nitritation with anaerobic ammonium oxidation) allow removing high ammonia concentrations via the nitrite route (Van Dongen et al, 2001). The SHARON-ANAMMOX concept gets much Manuscript revised Click here to download Manuscript: manuscript_revised.…”
Section: Introductionmentioning
confidence: 99%